2018
DOI: 10.4103/jispcd.jispcd_183_18
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical behavior of an implant system using polyether ether ketone bar: Finite element analysis

Abstract: Aim and Objectives:This study assessed, through finite element analysis, the biomechanical behavior of an implant system using the All-on-Four® technique with nickel–chromium (M1) and polyether ether ketone (PEEK) bars (M2).Materials and Methods:Implants and components were represented in three-dimensional (3D) geometric models and submitted to three types of load: axial, oblique, and load on all teeth. The 3D models were exported to a computer-aided design-like software such as Solidworks 2016 (Dassault Syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…After scrutinizing its properties, use of PEEK in fixed dental prosthesis is gaining popularity. Majority of the studies conducted till date are in vitro ,[ 3 4 5 6 7 8 9 ] and very few clinical studies[ 10 11 12 ] document the longevity of the restoration and its clinical performances. Although taking into consideration the favorable mechanical properties of PEEK, there is lack of acceptance.…”
Section: Introductionmentioning
confidence: 99%
“…After scrutinizing its properties, use of PEEK in fixed dental prosthesis is gaining popularity. Majority of the studies conducted till date are in vitro ,[ 3 4 5 6 7 8 9 ] and very few clinical studies[ 10 11 12 ] document the longevity of the restoration and its clinical performances. Although taking into consideration the favorable mechanical properties of PEEK, there is lack of acceptance.…”
Section: Introductionmentioning
confidence: 99%
“…In a Finite Element Analysis (FEA) study, the biomechanical behavior of an implant system utilizing the All-on-Four technique with nickel-chromium and PEEK bars was examined. This study revealed that PEEK bars exhibited the highest peak stresses [81] . Despite the limitations of clinical studies, it has been proposed that hybrid PEEK-acrylic resin prostheses supported by implants for full arch rehabilitation could be a feasible treatment option.…”
Section: Peek As a Removable Prostheses Materialsmentioning
confidence: 73%
“…A recent advancement in the field of PEEK involves the creation of hybrid PEEK-acrylic resin prostheses. These are being used in various dental restorative applications, including full arch implant-supported removable prostheses (with the female part of bars milled from PEEK), full arch implant-supported fixed prostheses, and the all-on-four concept [79][80][81] . In a Finite Element Analysis (FEA) study, the biomechanical behavior of an implant system utilizing the All-on-Four technique with nickel-chromium and PEEK bars was examined.…”
Section: Peek As a Removable Prostheses Materialsmentioning
confidence: 99%
“…In this work, the definitive CAD/CAM bars have been milled in PEEK. This choice is perfectly in tune with the metal-free philosophy, which is growing in digital dentistry; however, clinical studies are still needed to assess the performance and reliability of this material over the medium and long term [41]. In fact, although in this study all implants survived for one year, for a 100% survival rate, it should be noted that complications that were recorded during this study (two fixtures with peri-implantitis in the same patient and two repaired overdentures because of tooth fracture in two different patients) determined a success rate for the implant-prosthetic rehabilitation with overdenture of 80%, at 1 year.…”
Section: Discussionmentioning
confidence: 99%